China’s Pledge to Restore Blue Skies - Gong, Lina (2017)
The Chinese government declared a war to restore blue skies during the annual meeting of the National People’s Congress (NPC), China’s legislature, in March 2017. The increasing attention to air pollution by China’s leadership underscores the urgency of and the difficulty in addressing environmental issues, which is also shared by ASEAN countries.